1961
DOI: 10.1039/jr9610002455
|View full text |Cite
|
Sign up to set email alerts
|

473. Volatile products of pyrolysis of nicotine

Abstract: Jarboe ajzd Roserte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…The qualitative and quantitative data in are based on several studies (31,256,(289)(290)(291) and give some insight into the mechanism of fragmentation. The arbitrary values in the table are for use only in comparing relative yields of a given product from a given alkaloid at the indicated temperatures and do not reflect the absolute yields of products at one temperature.…”
Section: Carbohydrates Lignin and Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The qualitative and quantitative data in are based on several studies (31,256,(289)(290)(291) and give some insight into the mechanism of fragmentation. The arbitrary values in the table are for use only in comparing relative yields of a given product from a given alkaloid at the indicated temperatures and do not reflect the absolute yields of products at one temperature.…”
Section: Carbohydrates Lignin and Acidsmentioning
confidence: 99%
“…From this over-all pattern, it is evident that dehydrogenation, demethylation, and scission of the pyrrolidine ring are initial steps in the pyrolysis of nicotine. In a Ci-C2 fragmentation of this ring, dehydrogenation of the resulting N-methylaminoalkyl chain would give metanicotine (256) which, on further elimination, would form the observed 3-(l,3-butadienyl) pyridine and subsequently 3-vinylpyridine by appropriate cleavage. Fragmentation of the pyrrolidine ring in the 2,3 or 1,5 positions might ultimately give 3-cyanopyridine after dealkylation of the side chain.…”
Section: Carbohydrates Lignin and Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature the nicotine is thermally stable in an inert atmosphere up to 600 C [12,13]. No thermal stability information was found for the other two tobacco alkaloids; however, the DSC measurements performed did not indicate thermal instabilities in the measured temperature regions.…”
Section: Chemicalsmentioning
confidence: 91%
“…However, experimental studies have, as yet, not revealed the presence of specific urinary bladder carcinogens, such as naphthylamines, in cigarette smoke. Pyrolyses performed with many nitrogen compounds, tobacco alkaloids (Van Duuren et al, 1960;Jarboe and Rosene, 1961;Kobashi et al, 1963a, b, c) and amino acids (Heyns and Pavel, 1957;Ma1 et al, 1962), and analyses of the resultant pyrolyzates did not indicate the presence of naphthylamines. A different experimental approach seemed to be necessary to determine if bladder carcinogens can indeed be pyrosynthesized from nitrogen compounds.…”
mentioning
confidence: 99%